A educação infantil para crianças surdas em municípios da região metropolitana de Vitória - Rabelo, Dayane Bollis (2018)
This study it had as objective to analyze the conditions of implementation of the educative proposals in vigor for deaf children in the infantile education in cities of the metropolitan region of Vitória (ES), capital of Espírito Santo state. The study it was carried through in four cities of metropolitan region: Serra, Vila Velha, Cariacica and Vitória. As procedure of collection of the empirical material, national official documents and of the investigated cities that guide the education of children and, specifically of deaf people had been analyzed; as well as interviews semistructuralized with professionals of Secretariat of Education of these cities and centers of infantile education that possesses registered deaf children in the period where the field research was carried through. As theoretician-metodológico arrives in port, he was based in the description-cultural perspective of the human development, understanding that the human being if constitutes in social relations e, this context, its development occurs in the relation with the other, mediated for the language. Beyond media, the language is basic for the constitution of the thought. This perspective considers that the insertion of the child in the culture allows the development of superior psychic functions, amongst them the language, a system of signs that is created and transmitted socially. The research points that politics of education of distinct deaf people in national level and municipal theatres come being elaborated. However, many are the doubts and tensions found for the professionals who take care of these children in what the conceptualization says respect on the deafness, teaching of Brazilian language of signals (Libras in portuguese) and pedagogical practical one effectively education bilíngue. The research concluded that it has fragilities in the proposals of education for deaf children in the infantile education, in the investigated cities, over all in what it refers to to the formation of the professionals for the practical development of one educative one that recognizes and considers its especificidades. We evidence that efforts have been envidados aiming at to the education of these children, however, it has very what to be analyzed on the official orientações, practical pedagogical and its conditions of implementation for an education that recognizes its singularidades and makes possible they it constitution as subject, the participation in the culture, the appropriation of its language, at last, its integral development.